Trace Reconstruction: Generalized and Parametrized - Krishnamurthy, Akshay; Mazumdar, Arya; McGregor, Andrew; Pal, Soumyabrata (European Symposium on Algorithms, 2019)
In the beautifully simple-to-state problem of trace reconstruction, the goal is to reconstruct an unknown binary string x given random “traces” of x where each trace is generated by deleting each coordinate of x independently with probability p < 1. The problem is well studied both when the unknown string is arbitrary and when it is chosen uniformly at random. For both settings, there is still an exponential gap between upper and lower sample complexity bounds and our understanding of the problem is still surprisingly limited. In this paper, we consider natural parameterizations and generalizations of this problem in an effort to attain a deeper and more comprehensive understanding.